A study of the overnight use policy for reserve books in the U.P. Institute of Library Science - Moral, Reysa Celeste N. (2001)
The role of the library is to serve the educational and academic needs of its users especially the students. The ILS Library is among the many libraries in the University of the Philippines which seeks to uphold this vision. But how can the said library serve its users well if they are not in favor with the present library rules and procedures implemented particularly at the reserve section? One aspect of the current policies in the ILS Library reserve section that ILS students do not approved is the limited span of time allotted (overnight use). Students suggest to extend the time (overnight use) in borrowing books to satisfy their informational needs. Due to this situation, most students are not able to return the book on time and have to pay an overnight fine. For these students, the fines should be reduced to at least half of the present fines imposed which is five pesos per hour and fifty pesos per day. The ILS Library reserve section has limited copies of books which affect the borrowers as well as the librarian. The librarian should think of ways on how they can reproduce the book which are in demand. In connection with this, fifty students of the ILS served to support the study. Sixty (60) percent are not in favor of the present library rules and regulations of the ILS Library reserve section.